Bacterial Identification and Monitoring Around Two-Piece Dental Implants by Matrix-Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) - Saha, Sonali; Meenawat, Ajita; Sahu, Chinmoy; Srivastava, Vivek; Yadav, Shivam; Kumar, Vinod (Journal of Laboratory Physicians, 2020)
Context Early microbiological diagnosis and treatment of periodontal pathogens is important for successful retention of dental implants.Aims This study aimed to identify and monitor oral bacterial colonization after successful two-piece dental implants.Settings and Design In this study, 50 two-piece dental implant subjects were included and assessed clinically, radiographically, and microbiologically.Methods and Material All the parameters were recorded at various stages after prosthesis placement. In each stage, nonadherent (peri-implant sulcular fluid) and adherent (curetted inner threads) samples were collected. Semiquantitative anaerobic culture of the samples were done in Anoxomat system. Bacterial colonies were first identified by routine microbiological methods and then by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) method.Statistical Analysis All the results were analyzed by appropriate statistical methods (Chi-square, one factor analysis of variance, etc.).Results All the bacterial isolates were identified in the MALDI-TOF MS system with no failure. After implant placement for the nonadherent samples, the frequency (%) of Fusobacterium nucleatum, Prevotella melaninogenica, and Propionibacterium acnes decreased whereas frequency (%) of Escherichia coli, Staphylococcus epidermidis, and Streptococcus mitis increased. For adherent samples, the frequency (%) of E. coli, Enterococcus faecalis, Porphyromonas gingivalis, P. melaninogenica, and Veillonella parvula decreased, whereas frequency (%) of S. mitis and Streptococcus mutans increased. The postimplant mean nonadherent and adherent bacterial load increased with time but not significantly over the periods (p = 0.302 and 0.123, respectively).Conclusion Combination of basic (semiquantitative culture method) and advanced microbiological method (MALDI-TOF MS) can be useful for accurate detection and monitoring of potential pathogens around two-piece dental implants.
Keywords: dental implant; bacteria; MALDI-TOF MS; monitoring; culture